Characterization of Ca-phosphate biological materials by scanning transmission X-ray microscopy (STXM) at the Ca L2, 3-, P L2, 3- and C K-edges. (15th January 2015) - Cosmidis, Julie; Benzerara, Karim; Nassif, Nadine; Tyliszczak, Tolek; Bourdelle, Franck
Graphical abstract: Abstract: Several naturally occurring biological materials, including bones and teeth, pathological calcifications, microbial mineral deposits formed in marine phosphogenesis areas, as well as bio-inspired cements used for bone and tooth repair are composed of Ca-phosphates. These materials are usually identified and characterized using bulk-scale analytical tools such as X-ray diffraction, Fourier transform infrared spectroscopy or nuclear magnetic resonance. However, there is a need for imaging techniques that provide information on the spatial distribution and chemical composition of the Ca-phosphate phases at the micrometer- and nanometer scales. Such analyses provide insightful indications on how the materials may have formed, e.g. through transient precursor phases that eventually remain spatially separated from the mature phase. Here, we present scanning transmission X-ray microscopy (STXM) analyses of Ca-phosphate reference compounds, showing the feasibility of fingerprinting Ca-phosphate-based materials. We calibrate methods to determine important parameters of Ca-phosphate phases, such as their Ca/P ratio and carbonate content at the ∼25 nm scale, using X-ray absorption near-edge spectra at the C K-, Ca L2, 3 - and P L2, 3 -edges. As an illustrative case study, we also perform STXM analyses on hydroxyapatite precipitates formed in a dense fibrillar collagen matrix. This study paves the way for future research on Ca-phosphate biomineralization processes down to the scale of a few tens of nanometers.